Peran Pengendalian Internal Terhadap Fraud Triangle - A, Amelia; Karista, Erti (Fakultas Ekonomi, Universitas Cenderawasih, 2021)
Internal control is one of the means used to evaluate the effectiveness of the management of acompany. The purpose of internal control can be achieved when the elements of control itself arecompletely met and in order for the control within the company. The method used in this paper is aqualitative method that is descriptive in nature and uses analysis with several data sources andtheories that are used form several related sources: Based on the results of surveys and research bythe Association of Certified Fraud Examiners (ACFE) Global, it shows that every year an averageof 5% of the organization’s income becomes a victim of fraud. One of them is the case of StateOwned Enterprises (BUMN) that committed fraud. Internal control at BUMN that is still not goodat responding to corruption problems has resulted in fraud violations in BUMN. Because, this typeof fraud is often not detected because of the people who work together to enjoy the benefits. Asexplained AFCE. Of course this is related to weak and indecisive internal controls on theperpetrators of corruption within the BUMN itself. Through this internal control, the managementof the company can find out the extent to which the implementation of the company’s effectivenesshas been achieved, the problems that exist in the company as well as ways to overcome theseproblems. To prevent rampant fraud perpetrators in BUMN, SOEs must improve internal control bybuilding a good internal control structure and improving organizational culture with the principlesof fairness, transparency, creating effective supervision of employees and work units responsible forBUMN.